Investigating the relationship between self-efficacy and quality of life in Iranian women - Fatemeh Goldani Moghaddam; Nasrin Talkhi; Nooshin Peyman (BMC, 2024)
Abstract Background Women's quality of life and self-efficacy play pivotal roles in task accomplishment and overall health improvement within families and society. This study determination the intricate relationship between quality of life and self-efficacy among women utilizing care services from Mashhad health centers. Methods A cross-sectional study involving 366 women accessing Mashhad health centers in 2023 was conducted. Clustering sampling was employed, and data were gathered using the Schwartz self-efficacy questionnaire and the short form of quality of life. Statistical analysis utilized Spearman correlation coefficient, Kruskal-Wallis test, Mann-Whitney U-test, Wilcoxon test, and Chi-square test in SPSS25, with a significance level set at 0.05. Results Participants' mean age was 36.42 ± 11.13 years. A statistically significant relationship was observed between self-efficacy and total quality of life score, as well as its dimensions (physical health, psychological health, social relationships, social environment and quality of life, and general health) (P < 0.001). Conclusion The study underscores a significant association between self-efficacy and both the overall quality of life and its specific dimensions among women. These findings highlight the reciprocal influence of self-efficacy and quality of life. Consequently, tailored interventions aimed at enhancing self-efficacy and quality of life are recommended.